In-Situ Measurement of Thermal Diffusivity of Rock and Prediction Calculation of Transient Underground Climate - Mizuta Y; Biao Q (The Australasian Institute of Mining and Metallurgy, 1988)
Thermal constants such as thermal con- ductivity and thermal diffusivity of rock and coefficient of heat transfer of airway wall are the most important characteristic values which decide accuracy of prediction calcula- tion. However, quality of rock is not homoge- neous and water content in rock varies with location and so, a method for in-situ measure- ment of thermal constants must be taken in. The method developed by us is to measure in- situ rock temperatures at two different depths from airway wall. It is simple and we found its accuracy is good enough in the engineering Sense.